2009
DOI: 10.1080/19392690802628705
|View full text |Cite
|
Sign up to set email alerts
|

Briquetting of Coal Fines and Sawdust Part I: Binder and Briquetting-Parameters Evaluations

Abstract: Various technical and economic aspects relating to the briquetting of fine coal with sawdust have been evaluated with the results for two segments of that study presented here: binder and briquettingparameter evaluations. Approximately 50 potential binder formulations were subjected to a series of screening evaluations to identify three formulations that were the most cost effective for briquetting fine coal with sawdust. Two of the binders, guar gum and wheat starch, were selected as most suitable for the pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 2 publications
3
30
1
2
Order By: Relevance
“…When wood residue briquettes were combusted, HHV = 32.5 MJ kg -1 (Sotannde et al, 2010). Our results are a slightly lower, compared to the HHV of coal briquettes, being from 24.5 to 33.8 MJ kg -1 (Taulbee et al, 2009). We found the content of volatiles to be within the range 25-30%, while the share of ashes from burning of either T1 or T2 briquettes constituted 5-10%.…”
Section: Resultscontrasting
confidence: 39%
See 1 more Smart Citation
“…When wood residue briquettes were combusted, HHV = 32.5 MJ kg -1 (Sotannde et al, 2010). Our results are a slightly lower, compared to the HHV of coal briquettes, being from 24.5 to 33.8 MJ kg -1 (Taulbee et al, 2009). We found the content of volatiles to be within the range 25-30%, while the share of ashes from burning of either T1 or T2 briquettes constituted 5-10%.…”
Section: Resultscontrasting
confidence: 39%
“…Further technical and economic aspects of fine coal and charcoal briquettes have been evaluated because of the binder and briquetting parameters. Briquetting pressure and dwell time have a weak impact, while binder type and curing conditions exert the greatest influence on briquettes quality (Borowski and Hycnar, 2013;Taulbee et al, 2009). What is more, mechanical properties increase with time of curing at room temperature of carbonized-coal briquettes (Blesa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The biomass particle size is inversely proportional to the density which results from larger contact area effects in smaller particles and better density [3][4][5][6]. Such particles in the conditioning process more easily absorb the steam and thus cause greater influence of gelatinize the starch and increase the productivity and reduce the cost and improve the agglomeration stability of the pellets.…”
Section: Resultsmentioning
confidence: 99%
“…Particles of smaller size have a greater contact area and are easier to package during compaction [1][2][3][4][5][6]. Higher surface area increases number of contact points for chemical reactions [7], which may require grinding to a nominal particle size of about 1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The approaches toward the pretreatment [4][5][6][7] of low rank coal have been very diverse, but the commonly used pretreatment method is thermal treatment. Zeng et al [8] investigated the effects of thermal pretreatment in helium on the pyrolysis behavior of Loy Yang brown coal and found that preheating the brown coal at N523 K leads to reduced tar and increased char yields.…”
Section: Introductionmentioning
confidence: 99%